Speak so your audience will listen 7 steps to confident and successful public speaking - Kermode, Robin (London Pendle, 2013)
SPEAK (so your audience will listen) is a book for anyone who has to deliver a message, tell a story - or speak to another human being. Most of us are quite relaxed and confident when we're with our friends and family. We can tell a story or even tell a joke. But put us on a platform and we can feel very different. When we speak to an audience, we often put on a public mask ? and use a different voice. Why can?t we seem to be ourselves when we give a talk? In this book we will look at all aspects of spoken communication, from structure right through to delivery. We will learn how to have a conversation with our audience - to be ourselves - so that we connect with them every time we speak. In 7 simple steps you can learn to be a confident and successful public speaker. There are specific exercises at the end of every section for you to practice. Whether you?re a CEO presenting to shareholders, a manager motivating your team, an entrepreneur selling a business, a creative pitching an idea, a charity worker asking for donations or a parent speaking at your daughter?s wedding, this book will help you become a confident and successful public speaker, so that when you speak, your audience will listen. And, hopefully, you'll enjoy the experience too.
Keywords: Public Speaking